(untitled) (Eurasian Journal of Philology Science and Education, 2016)
This article is devoted to study individually-authorial world perception features, reflected in artistic text on the material of M. Auezov’s drama. As it is generally known, the world view in artistic text is created by language means, here it reflects the individual world view in the writer’s consciousness and realized in the selection of elements of artistic work maintenance, language means, and individual use of figurative means. The Individually-authorial world view, reflected in artistic text, carries status artistic and language, because the question is about literary work, where a language serves as the means of creation of the artistic world. It is considered, how originality of national picture of the world, basic features of national mentality of the Kazakh people, and also individually-authorial world view of the writer are reflected in the works of М. Аuezov. Also language units, performing the characterizing duty, thus answering the disclosure of the image of the hero are studied in it.